POLICY IMPLEMENTATION ON INTEGRATED REFERRAL SERVICE SYSTEM PROGRAM OF POVERTY ALLEVIATIONIN BANDUNG CITY, WEST JAVA, INDONESIA - Andre Ariesmansyah; Dea Melati (International Journal of Social Science, 2021)
Integrated Referral Service System (IRSS) program is a service system to assist the poor in their needs through poverty reduction and social protection programs. One of them is the government makes a program or policy to be able to serve various social services in reducing poverty. It was found that the implementation of the Integrated Referral Service System program policy in its implementation involved legal rules and other regional regulations. This study aims to determine and describe the extent of policy implementation in the Integrated Referral Service System program at the Bandung City Social Service. This research report discusses the implementation of policies regarding the Integrated Referral Service System program, the obstacles faced and the efforts made by the Bandung City Social Service through the Puskesos assistant for Integrated Referral Service System implementation or facilitators in the Maleber village. The research method used in this method is a qualitative research method. Data collection techniques used are observation, interviews, and documentation. This research is a comparison in policy implementation is the theory of David L. Weimer and Aidan R. Vining (2014) namely Policy Logic, Environment in which Policy is Operated, and Implementor Capability. There were four informants in this study, namely the Head of Protection and Social Security, Head of the Service and Referral Section, Integrated Referral Service System of Implementing Facilitators and people who use Integrated Referral Service System. The conclusions drawn in this study are based on indicators that the Policy Implementation regarding the Integrated Referral Service System program in Bandung City through the Social Health Center in Maleber Village from 2019 to 2020 experienced a fairly high increase. Due to the large number of poor and underprivileged people who need assistance in the form of complaints about social problems, especially the impact of the covid 19. Poverty Reduction at the Bandung City Social Service is quite optimal, it's just that there are some obstacles regarding infrastructure and understanding in carrying out various complaints and services to the public. Integrated Referral Service System Health Center Scores.